Waste to Energy: An Assessment of Application of the Selective Fuel for Applications in Industries using a Mixture of "A" Grade Coal and Municipal Solid Waste - Bajracharya, Nripendra; Ale, Bhakta Bahadur; Singh, Ramesh Man; Bajracharya, Tri Ratna (Journal of the Institute of Engineering, 2017)
This paper is about how the garbage that is considered as nuisance can actually be a source of energy that is vital for us. The fuel prepared by blending combustible fraction of waste is called refuse derived fuel (RDF). When the waste is mixed with coal known as selective fuel, they can be the replacement for coal in industries. The vertical shaft brick kiln (VSBK) has been taken as a representative of industrial sector. This is the theme of this research. The coal sample used is from Assam, India which is the A grade coal normally used in VSBKs of Nepal. The selective fuel was undergone proximate analysis, smoke index test, flue gas emission test and was also tested for its calorific value. The moisture content and ash content is found to be 8.69% and 11.21% respectively which is the acceptable range for VSBK. The fixed carbon content of the fuel is 28.03%. The sulphur content of the coal is 6.4% which can be captured using Ca(OH2. Addition of lime and presence of excess air help to control smoke during combustion. Flue gas emission test shows CO emission of 56.66 ppm, CO2 emission of 2% and no SO2 emission. The economic analysis shows that installation of small scale briquetting plant is feasible. Besides this, mathematical calculation has also been done to deduce some results. Journal of the Institute of Engineering, 2016, 12(1): 129-142